Folic Acid Therapy Reduces the First Stroke Risk Associated With Hypercholesterolemia Among Hypertensive Patients. Issue 11 (November 2016) - Qin, Xianhui; Li, Jianping; Spence, J. David; Zhang, Yan; Li, Youbao; Wang, Xiaobin; Wang, Binyan; Sun, Ningling; Chen, Fang; Guo, Jingxuan; Yin, Delu; Sun, Liming; et al.
Abstract : Background and Purpose—: We sought to determine whether folic acid supplementation can independently reduce the risk of first stroke associated with elevated total cholesterol levels in a subanalysis using data from the CSPPT (China Stroke Primary Prevention Trial), a double-blind, randomized controlled trial. Methods—: A total of 20 702 hypertensive adults without a history of major cardiovascular disease were randomly assigned to a double-blind daily treatment of an enalapril 10-mg and a folic acid 0.8-mg tablet or an enalapril 10-mg tablet alone. The primary outcome was first stroke. Results—: The median treatment duration was 4.5 years. For participants not receiving folic acid treatment (enalapril-only group), high total cholesterol (≥200 mg/dL) was an independent predictor of first stroke when compared with low total cholesterol (<200 mg/dL; 4.0% versus 2.6%; hazard ratio, 1.52; 95% confidence interval, 1.18–1.97; P =0.001). Folic acid supplementation significantly reduced the risk of first stroke among participants with high total cholesterol (4.0% in the enalapril-only group versus 2.7% in the enalapril–folic acid group; hazard ratio, 0.69; 95% confidence interval, 0.56–0.84; P <0.001; number needed to treat, 78; 95% confidence interval, 52–158), independent of baseline folate levels and other important covariates. By contrast, among participants with low total cholesterol, the risk of stroke was 2.6% in the enalapril-only group versus 2.5% in the enalapril–folic acid group (hazard ratio, 1.00; 95% confidence interval, 0.75–1.30; P =0.982). The effect was greater among participants with elevated total cholesterol ( P for interaction=0.024). Conclusions—: Elevated total cholesterol levels may modify the benefits of folic acid therapy on first stroke. Folic acid supplementation reduced the risk of first stroke associated with elevated total cholesterol by 31% among hypertensive adults without a history of major cardiovascular diseases. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00794885. Abstract : Supplemental Digital Content is available in the text.